FIRST RECORD OF Xenicola dohrni (BRUNNER VON WATTENWYL, 1891) (TETTIGONIIDAE, PHANEROPTERINAE, ODONTURINI) FOR URUGUAY (Boletín de la Sociedad Zoológica del Uruguay, 2022)
The genus Xenicola is represented in South America by five species of small katydids that are distributed from southern Brazil to central Argentina. We report that genus for Uruguay for the first time, with the species Xenicola dohrni (Brunner von Wattenwyl, 1891).
Keywords: katydids; taxonomy; South America